Evaluation of inadequate, indeterminate, false-negative and false-positive cases in cytological examination for breast cancer according to histological type - Yamaguchi Rin; Tsuchiya Shin-ichi; Koshikawa Takashi; Yokoyama Toshiro; Mibuchi Kuniko; Nonaka Yasuhide; Ito Sonoe; Higuchi Hidejiro; Nagao Mariko; Higaki Koichi; Watanabe Jiro; Kage Masayoshi; et al. (BMC, 2012)
Abstract Background We previously investigated the current status of breast cytology cancer screening at seven institutes in our area of southern Fukuoka Prefecture, and found some differences in diagnostic accuracy among the institutions. In the present study, we evaluated the cases involved and noted possible reasons for their original cytological classification as inadequate, indeterminate, false-negative and false-positive according to histological type. Methods We evaluated the histological findings in 5693 individuals who underwent cytological examination for breast cancer (including inadequate, indeterminate, false-negative and false-positive cases), to determine the most common histological types and/or features in these settings and the usefulness/limitations of cytological examination for the diagnosis of breast cancer. Results Among 1152 cytologically inadequate cases, histology revealed that 75/173 (43.6%) cases were benign, including mastopathy (fibrocystic disease) in 38.6%, fibroadenoma in 24.0% and papilloma in 5.3%. Ninety-five of 173 (54.9%) cases were histologically malignant, with scirrhous growing type, invasive ductal carcinoma (SIDC) being significantly more frequent (49.5%) than papillotubular growing type (Papi-tub) (P < 0.0001), solid-tubular growing type (P = 0.0001) and ductal carcinoma in situ (DCIS) (P = 0.0001). Among 458 indeterminate cases, 54/139 (38.8%) were histologically benign (mastopathy, 30.0%; fibroadenoma, 27.8%; papilloma, 26.0%) and 73/139 (52.5%) were malignant, with SIDC being the most frequent malignant tumor (37.0%). Among 52 false-negative cases, SIDC was significantly more frequent (42.3%) than DCIS (P = 0.0049) and Papi-tub (P = 0.001). There were three false-positive cases, with one each of fibroadenoma, epidermal cyst and papilloma. Conclusions The inadequate, indeterminate, false-negative and false-positive cases showed similar histological types, notably SIDC for malignant tumors, and mastopathy, fibroadenoma and papilloma for benign cases. We need to pay particular attention to the collection and assessment of aspirates for these histological types of breast disease. In particular, several inadequate, indeterminate and false-negative cases with samples collected by aspiration were diagnosed as SIDC. These findings should encourage the use of needle biopsy rather than aspiration when this histological type is identified on imaging. Namely, good communication between clinicians and pathological staff, and triple assessment (i.e., clinical, pathological and radiological assessment), are important for accurate diagnosis of aspiration samples. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/7349809170055423